Auschwitz lullaby [large type] - Escobar, Mario, 1971- (Center Point Large Print, 2019)
"Based on the true story of a brave German nurse tasked with caring for Auschwitz's youngest prisoners, Auschwitz Lullaby brings to life the story of Helene Hannemann--a woman who sacrificed everything for family and fought furiously for the children she hoped to save"--